(untitled) (Academia Journal of Medicine, 2018)
Background: Cardiovascular diseases (CVD) have emerges as the leading cause of mortality throughout the world. Essential hypertension is one of the important risk factor for CVD in modern society despite advanced and effective management. Malondialdehyde (MDA) is a well known marker of oxidative stress, which is produced by oxidation of poly unsaturated fatty acid. Nadishodhan pranayam leads to decrease stress as well as blood pressure. Subjects and Methods: It was an interventional type of study. Ninety seven mild hypertensive patients (53 males and 44 females) of group I completed the yoga program. While, fifty normotensive subjects were include as control in group II. Blood pressure and MDA was measured of every participants before and after three months of yoga program. Results: Total ninety seven mild hypertensive patients of age 33.6± 8.66 years of group I completed three months yoga program. However, fifty subjects (34.7± 7.73 years)of group II had not done any yogic exercise during three months. Results of the present study showed that there was a significant difference in SBP (p<0.001), DBP (p<0.001), HR (p<0.001), PP (p<0.001) and MAP (p<0.001) group I mild hypertensive patients after following three months yoga program. There was a significant difference between before and after yoga program MDA level of group I mild hypertensive patients. However, there was an insignificant difference between before and after three months level of MDA in group II control subjects. Conclusion: In this study, it has been observed that daily practice of yoga improves the blood pressure of mild hypertensive patients. Moreover, it substantially decreases the oxidative stress. Yoga can be an effective alternative to reduce the blood pressure in mild hypertensive patients either with medication or without medication.